Pendapat Pimpinan Universitas Swasta Tentang Manfaat Media Sosial Bagi Kinerja Profesi Public Relations - Neni Yulianita; M.E. Fuady (Postgraduate of Jayabaya University, 2015)
Many enthusiasts to the private university turned out to have consequences for the role of the managers to play their functions, particularly in promoting the university through various media are used as a tool in providing information, ad serving, doing publicity, and so on. The method used is survey method through the study of quantitative approach path analysis. The study population was faculty leaders on eight private universities in West Java. Results of this study certainly expected to be useful and provide input to the profession of Public Relations (PR) private university in West Java in an effort to build relationships with the public through the use of social media as a positive and favorable in order to improve the quality of relationships with its stakeholders and produce the findings of new data and information that are useful for PR private university related to the use of social media.